Engineered electrospun poly(lactic-co-glycolic acid)/Si3N4 nanofiber scaffold promotes osteogenesis of mesenchymal stem cell - Zhou, Changsong; Su, Shenghui; Fan, Jiwen; Lin, Jiuzao; Wang, Xiaoyong (Frontiers in Materials, 2022)
Nanofibers hold promising pathways in bone tissue engineering scaffold (BTES). In this study poly (lactic-co-glycolic acid) (PLGA)/ silicon nitride (Si3N4) composite nanofiber membranes electrospinning were formed and osteogenesis capability of mesenchymal stem cells (MSC) of the scaffold marrow was investigated. By modifying different properties of Si3N4 to PLGA, two hybrid scaffolds were successfully prepared, including the PLGA/Si3N4 (1 wt.%) nanofiber scaffold and PLGA/Si3N4 (2 wt.%) nanofiber scaffold. The diameter of the fiber nanofiber scaffold PLGA/Si3N4 decreased, while the mechanical strength increased compared to PLGA. In vitro studies showed better cell adhesion, and proliferation of PLGA/Si3N4 nanofiber scaffold than PLGA nanofiber scaffold. Integration of Si3N4 promoted osteogenesis capacity by increasing gene expression of bone-related proteins (such as BMP2, ALP, OPN, COL1a1, Runx2 and OCN), more calcium deposits and support of ALP activity compared to PLGA nanofiber scaffold. Similarly, PLGA/Si3N4 (2 wt.%) nanofiber scaffold showed better performance than PLGA/Si3N4 (1 wt.%) nanofiber in mechanics and biological activity. Overall, PLGA/Si3N4 nanofiber scaffold has the potential to develop as a promising hybrid scaffold for bone regeneration.